Time-motion analysis in fencing competition - Sanhueza Alfaro, S.; Rodio, A.; Terranona, A.; Cortis, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Fencing is a situation sport where two athletes fight in a continuous strategy game, masking their true intentions to surprise and hit the opponent. Fencing is generally classified as open-skill sport (Dal Monte et al 1980), characterized by a very high energy demand (Caldarone et al 1983; Nystrom et al 1990), closely linked to the atlethes` coordinative and psychological characteristics (Sapega et al 1984). Within each competition there is a wide variability of actions duration, represented by numerous stopping and starting phases. Since the understanding of the complex multi-dimensional model of fencing requires a careful analysis of the various aspects of performance. The aim of this study was to analyze the time-motion structure of fencing competitions. Methods: Eighteen male (n=9) and female (n=9) of 36 male (n=18) and female (n=18) italian epee fencers were recorded during the 2013 National University (age:20-28) Championship. Duration (s) of fighting and nonfighting phases were recorded in all matches (5 touches for a maximum of 3 min), using Dartfish TeamPro Software. Differences (p<0.05) were analyzed in relation to gender (male vs female) and type of action (fighting vs nonfighting) through Analysis of Variance. Results: Regardless of gender, higher (p<0.05) duration were found during fighting (male:15.2±13.6s; female: 14.1±9.8s) phases with respect to nonfighting (male:7.3±4.1s; female:5.9±4.4s) ones. Discussion: Findings indicate a longer duration of atlete fighting actions with respect nonfighting ones, independently from gender. This would probably depend to a strategic choice dictated by the preliminary stage of the competition, where the short duration of the match allows athletes to spend more time in fighting phase, in order to be able to get 5 touches before their opponent.